O prawnych problemach ustalania linii zabudowy w polityce przestrzennej. Analiza orzecznictwa sądów administracyjnych = On legal problems in establishing building lines in spatial policy. Analysis of the verdicts of administrative courts - Szlachetko, Jakub H. (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Building lines, which define the legally allowable distance between the front wall of buildings and streets, are an essential element of spatial policy. One should risk the thesis that the correct defining of building lines in local area plans or in individual building regulations is a condition for an effective spatial policy. Unfortunately, the analysis of actual acts of spatial policy reveals that planning authorities waive the establishment of the building line, or define it incorrectly, which has negative consequences for urban planning and architecture. In this article, the main legal problems regarding the establishment of the building line are discussed using statutory regulations and, primarily, verdicts of administrative courts.
Keywords: planowanie przestrzenne; miejscowy plan zagospodarowania przestrzennego; decyzja o warunkach zabudowy; linia zabudowy; obowiązująca linia zabudowy; nieprzekraczalna linia zabudowy; spatial planning; local area plan; individual building regulations; building line